Application of Refined Nursing Combined with Comprehensive Treatment of Traditional Chinese and Western Medicine in Gastrointestinal Dysfunction after Tumor Operation. (20th July 2022) - Su, Hongqing; Wen, Yuexian; Kang, Dandan
Abstract : After surgical treatment, the gastrointestinal function of tumor patients is inhibited for a short time. Refined nursing is beneficial to the recovery of gastrointestinal function of tumor patients after operation. Traditional Chinese medicine and Western medicine have their own advantages in the treatment of gastrointestinal dysfunction after tumor operation and the combined application of the two is more ideal. Therefore, on the premise of refined nursing, we should carefully study the efficacy of integrated traditional Chinese and Western medicine in the treatment of postoperative gastrointestinal dysfunction in tumor patients. Fifty patients with gastrointestinal dysfunction after tumor surgery admitted to Xiamen University Affiliated Zhongshan Hospital from June 2021 to August 2022 were retrospectively selected. Twenty two of them received refined care + Western medicine (control group, CG) and the other 28 received refined care + Western medicine + moxibustion and thumb-tack needle Chinese medicine (observation group, OG). We compared the recovery of gastrointestinal function, inflammatory factors, negative emotions, sleep quality, length of stay, medical expenses, and adverse reactions. The postoperative recovery effect of gastrointestinal function in the OG was better than that in the CG. The IL-8 level and TNF - α level in OG were lower than those in CG. Relative to CG, the OG had significantly low SDS scores, SAS scores, PSQ1 scores, length of hospital stay, and medical expenses. The OG incidence of adverse reactions was 28.57%; it was significantly lower than 59.09% in the CG. Refined nursing with integrated Chinese and Western medicine therapeutic interventions can promote the recovery of gastrointestinal tract function, relieve anxiety and depression, and improve sleep quality in patients with postoperative gastrointestinal dysfunction after tumor surgery.